DIGITAL READING DURING THE PANDEMIC: EXPLORING VOCATIONAL STUDENTS’ PERCEPTIONS - Purwaningrum, Diana; Suhaeni, Suhaeni; Pramesti, Rahandika Mita; Agustina, Anisa; Juwita, Rahmi; Hanum, Zakiah; Putri, Salyantissa; Udin, Noor; Hartono, Hendri; Prakoso, Emmanuel Putro; Udiono, Tangkas; Suranto, Didik (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This study was aimed at exploring vocational school students’ perceptions of their digital reading during the pandemic and their utilization of various digital media. The participants were eight students from three public vocational schools in Semarang, Central Java. This study adopted a qualitative descriptive method to explore vocational students’ perceptions of digital reading in times of COVID-19 pandemic. Data were gathered through an online semi-structured interview, in which the recording was transcribed and analyzed from the lens of multimodality. The study revealed that during the pandemic, vocational school students reported their difficulties in reading vocational materials in digital files, especially in the portable document format (pdf). The major influencing factors were the rigidity of learning materials in the pdf, the lack of peer interactions after digital reading, and the teachers’ pedagogical moves that might obstruct the development of digital reading skills. In contrast, this study reported that students utilized a plethora of digital media, websites, and applications, including Tiktok, Instagram, Wattpad, and Webtoon to read a wide variety of topics that capture their interests, from social, politics, economics, and romance. This study underlines the importance of enhancing student skills in digital reading in vocational subjects by utilizing various digital media.